Relação produtividade-diversidade taxonômica e funcional da comunidade zooplanctônica em reservatórios tropicais - Amaral, Camila Bezerra (2025)
The objective of this study was to identify the relationship between productivity and the taxonomic and functional diversity of the zooplankton community in tropical reservoirs. The study was conducted in reservoirs located in Northeast Brazil. We used chlorophyll-\(a\) as a measure of productivity and taxonomic and functional diversity indices for zooplankton diversity. The results demonstrate that the increase in phytoplankton productivity, measured by chlorophyll-\(a\), is a central factor in reducing zooplankton diversity, acting as a selective environmental filter. Overall, increased productivity was associated with a decline in taxonomic diversity, with consistent negative linear relationships for groups such as cladocerans. For the functional diversity of the community as a whole, the relationship with productivity was unimodal for functional divergence. Statistical analyses identified that some species (three cladocerans and one rotifer) responded negatively to the productivity gradient, while one copepod species showed a positive association. Furthermore, productivity, intensified by higher temperatures and phosphorus concentrations, especially in semi-arid climates, is the main driver structuring these communities, explaining a significant portion (18%) of the reduction in functional diversity. Therefore, controlling eutrophication through nutrient management is crucial for the conservation of zooplankton biodiversity in these vulnerable tropical aquatic ecosystems. These findings highlight the importance of considering both taxonomic and functional heterogeneity when assessing the response of the zooplankton community to productivity, providing insights into how diversity responds to this productivity. This is especially relevant in warmer regions, where productivity and physico-chemical water quality need to be monitored to ensure the conservation of zooplankton biodiversity.